IMPLEMENTASI STANDAR AKUNTANSI KEUANGAN TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA LAPORAN KEUANGAN KOPERASI SERBA USAHA ”AKEN MITRA SEJATI” CAKRANEGARA - UTAMI, LUH; FITRI, SYARIFAH MASSUKI; SAPUTRA, ZULFIKRI SATRIAWAN (GANEC SWARA, 2023)
Cooperatives as economic entities make financial reports as a means of accountability to members and cooperative management. Cooperative financial reporting is regulated in the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). Considering that the need to prepare and present financial reports guided by SAK ETAP greatly influences the continuity of cooperative businesses, therefore this research aims to analyze the extent of implementation of SAK ETAP in the preparation and presentation of financial reports of KSU "Aken Mitra Sejati" Cakranegara. The research approach is descriptive qualitative which compares the preparation and presentation of financial reports in cooperatives with the provisions contained in SAK ETAP. Data analysis was carried out by describing the data found in the cooperative and then comparing it with SAK ETAP. The research results show that the Aken Mitra Sejati Cakranegara Multi-Purpose Cooperative has not fully implemented the preparation of financial reports in accordance with SAK ETAP